Enhancing Gross Motor Skills in Children Aged 5-6 Through Outbound Games - Eka Nurhalisa; Muzakki Muzakki; Ali Iskandar Zulkarnain; Mariatul Kiptiyah; Marco brambila (Universitas Islam negeri Mahmud Yunus Batusangkar, 2024)
Gross motor skills are the ability to carry out activities with large muscles. This study aims to determine the effect of outbound games on the gross motor skills of children aged 5-6 years . This research used a PTK type of research carried out in 2 cycles with research subjects of 10 children aged 5-6 years. The success criterion is 80% as the basis for whether the research carried out was successful or not. The results of the research show that in the pre-cycle, children's abilities on average develop very well with indicators that children can carry out balance movements, control and agility, children can play games with rules, children can coordinate eyes, hands and feet, children can walk according to directions. with an average percentage obtained of 20%, in cycle I it increased to a percentage of 48% with very well developed criteria (BSB) and in cycle II it was obtained at 81.4%, an increase because it had reached 80%, so this research was.┬á┬á